Spletno in mobilno nadlegovanje: pojem, oblike, posledice in soočanje s kazenskim pravom - Završnik, Aleš (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2013)
The article analyses cyberbullying and its multifaceted nature that refers to bullying and harassment of others by means of new electronic technologies, primarily mobile phones and the Internet. It presents consequences and dangers of cyberbullying and continues by focusing on possible avenues of interventions against cyberbullying, specifically on disciplinary rules within educational setting, specifically primary schools, and criminal law. It analyses new characteristics of cyberbullying, such as anonymity of perpetrator, greater scale of audience and its boundless nature crossing existing time-space borders that are turning cyberbullying into new type of deviance. It concludes by focusing on avenues of criminal prosecution of cyberbullies under Slovenian Criminal Code and proposes its changes de lege ferenda.
Keywords: kazniva dejanja; elektronski kriminal; svetovni splet; zasebnost; privacy; kršenje